2018
DOI: 10.1016/j.pmrj.2018.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Development and Persistence of Suspected Neuropathic Pain After Total Knee Arthroplasty in Individuals With Osteoarthritis

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…10 Similar results were found in another prospective study following total knee arthroplasty. 5 The results of our study suggest that a significant amount of foot and ankle patients, both for acute injuries and chronic conditions, have NP symptoms. The implication of that on their results is yet to be evaluated.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…10 Similar results were found in another prospective study following total knee arthroplasty. 5 The results of our study suggest that a significant amount of foot and ankle patients, both for acute injuries and chronic conditions, have NP symptoms. The implication of that on their results is yet to be evaluated.…”
Section: Discussionmentioning
confidence: 59%
“…A recent general-population health survey done in the United States found that as high as 15.7% of the patients reporting to have pain and 10% of all the responders had a probable NP with a higher tendency in certain ethnic groups (blacks and Hispanic). 2 The study of NP in orthopedic conditions has started with focusing mainly in osteoarthrosis (OA) of the knee 1,5,7,14,16 and spinal pathologies 15,23 but has now progressed to evaluate the prevalence and the implications of NP in other common orthopedic conditions including hip lesions, 13 rotator cuff tear, 9 carpal tunnel syndrome, 18 etc. These studies have found up to 34% of the patients with knee OA have NP, 10.5% of the patients with carpal tunnel syndrome, 15.8% with rotator cuff tears, and as high as 53% of patients with chronic back pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, previous studies did not evaluate the outcomes after TKA in patients with neuropathic pain, the present study demonstrated the key role of preoperative possible neuropathic pain on postoperative pain. Using the Self-administered Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) scale, Fitzsimmons et al [19] reported that suspected neuropathic pain was present in 35.5% of pre-TKA patients, and in 23.6% of OA patients at 6 months post-TKA. Patients scoring 12 or greater on the scale were de ned as having suspected neuropathic pain [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using the Self-administered Leeds Assessment of Neuropathic Symptoms and Signs (S-LANSS) scale, Fitzsimmons et al [19] reported that suspected neuropathic pain was present in 35.5% of pre-TKA patients, and in 23.6% of OA patients at 6 months post-TKA. Patients scoring 12 or greater on the scale were de ned as having suspected neuropathic pain [19]. If surgeons recognize the presence of possible neuropathic pain before TKA, careful evaluation, including of spinal disease, is needed to avoid chronic postoperative knee pain.…”
Section: Discussionmentioning
confidence: 99%